Karakteristik Biodegradable Film Komposit Berbahan Pati Termodifikasi-Nanokitosan-Glukomanan dengan Penambahan Plasticizer Gliserol dan Sorbitol - Syahla Salsabila; Pepita Haryanti; Condro Wibowo (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
The starch-based film is known to exhibit poor mechanical properties. Combining multiple materials as composite could be an alternative solution to the problem. The suitability of ratios between modified cassava starch, chitosan, and glucomannan as composite film with addition of sorbitol or glycerol was studied further to analyze physical, chemical, barrier properties of biodegradable films created. The research was conducted in a completely randomized design with twelve treatments. The treatment used different ratios of biodegradable composite film formulation (1:1:1, 1:1.4:0.6, and 1:0.4:1.6) and the addition of plasticizers (1%, 2% glycerol, and sorbitol). The water vapor transmission rate gave a significant value (P 0,05) for all factors tested, while thickness is significantly affected by the different ratios of film formulation. The results show that the film thickness ranged between 0.13 - 0.20 mm, and the water vapor transmission rate was 2.05 - 13.39 g/m2.hour. Based on these values, it was found that formulation 1, with a ratio of 1:1:1 added with 2% sorbitol, produced a film with better mechanical properties with excellent qualities such as moisture content, color, optical properties, and biodegradability. Thus, it could be recommended as an alternative for food packaging.